The sub-fascial pattern of the myocutaneous platysma flap – The anatomical basis and preliminary cases for oral reconstruction. Issue 3 (March 2022) - Hakim, Samer G.; Steller, Daniel; Falougy, Mohamed; Tharun, Lars; Sieg, Peter; Ciocan-Pendefunda, Constantin
Abstract: To verify the feasibility of the SF-MPF for oral reconstruction, the anatomic, sonographic and histologic features of the SF-MPF were investigated and the outcome in a series of patients was evaluated. The sonographic and histologic results showed a supra-fascial arterio-venous vascular blood supply to the sub-fascial design of the MPF. The clinical course of 12 consecutive patients who underwent oral reconstruction using the SF-MPF along with ipsi- or lateral neck dissection for treatment of oral cancer showed sufficient pedicle length and reliable blood supply. The SF-MPF is a reliable and safe pedicled myocutaneous flap. Therefore, it should be considered being an additional option when a pedicled flap has to be selected. Graphical abstract: Image 1